The Effect Of Continuity Of care On Postpartum Women’s Health - Liberty Barokah; Dewi Zolekhah; Silvia Ari Agustina (Jurnal EduHealth, 2023)
Continuity of care (CoC) is a midwifery service through a continuous service model for women throughout pregnancy, childbirth, postpartum and family planning. The design used is a quasi experiment with the Posttest-Only Control Design method. The sample size was 208 postpartum women divided into two groups. The group that was assisted was 104 respondents and the control group was 104 respondents. The statistical test used was the Mann Whitney test. Result: the majority of respondents were at reproductive age (74,6%), most respondents were 2-3 times gravida (58,33%), there were 46 (19,16%) postpartum women who experienced problems and complications. The most postpartum problems and complications were nipple blisters, there were 27 postpartum women (11.3%), there is a significant difference between complications and danger signs of puerperium between groups given continuous care and those not given continuous care (p = 0.000). Conclusion : Continuity of care affects the health of postpartum women. Postpartum complications and danger signs can be minimized because if there are postpartum complications and danger signs, they have been detected from the beginning of the postpartum period.